Serum cystatin C and βeta-2 microglobulin as potential biomarkers in children with lupus nephritis - Eman Baraka; Nashwa Hashaad; Walid Abdelhalim; Gehan Elolemy (Archives of Rheumatology, 2023)
Objectives: In this study, we aimed to assess serum levels of Cystatin C (Cys C) and beta-2 microglobulin (β2M) in juvenile systemic lupus erythematosus (JSLE) patients and to investigate their role as potential biomarkers of lupus nephritis (LN) and overall disease activity. Patients and methods: Between December 2018 and November 2019, a total of 40 patients with JSLE (11 males, 29 females; mean age: 12.6±2.5 years; range, 7.5 to 16 years) and 40 age- and sex-matched controls (10 males, 30 females; mean age: 12.3±2.4 years; range, 7 to 16 years) were included in this study. Serum (s) Cys C and β2M levels were compared between the groups. The SLE Disease Activity Index (SLEDAI-2K), the renal SLEDAI (rSLEDAI), and the Renal Damage Index were used. Results: JSLE patients had significantly elevated mean sCyc C and sβ2M levels (1.4±0.8 mg/mL and 2.8±0.9 mg/mL, respectively) compared to the controls (0.6±0.1 mg/mL and 2.0±0.2 mg/mL, respectively; p<0.00). The mean sCys C and sβ2M levels were significantly higher in the LN group, compared to non-LN patients (1.8±0.7 mg/mL and 3.1±1.0 mg/mL, respectively vs. 0.8±0.3 mg/mL and 2.4±0.6 mg/mL, respectively; p=0.002 and p=0.02, respectively). The sCys C levels had significant positive correlations with erythrocyte sedimentation rate (r=0.3, p=0.05), serum creatinine (r=0.41, p= 0.007), 24-h urinary protein (r=0.58, p<0.001), anti-double stranded deoxyribonucleic acid antibodies titers (r=0.55, p=0.002), extra-renal SLEDAI scores (r=0.36, p=0.04), rSLEDAI (r=0.46, p=0.002), and renal class (r=0.7, p=0.0001). Serum β2M levels were significantly negatively correlated with complement 4 levels (r=-0.31, p=0.04) and significantly positively correlated with extra-renal SLEDAI scores (r=0.3, p=0.05). Conclusion: These findings confirm that sCys C and sβ2M levels are increased in JSLE patients in association with the overall active disease. However, sCys C level may act as a promising non-invasive biomarker for predicting kidney disease activity and biopsy classes in children with JSLE.